Simulation based dynamic laser stimulation for failure analysis of analog and mixed-signal circuits. (November 2021) - Melis, T.; Simeu, E.; Saury, L.; Auvray, E.
Abstract: With the increasing complexity of circuits, it is difficult to carry out fault isolation in a short time. This is particularly true for mixed-signal circuits when using only standard fault isolation techniques (e.g. EMMI or TLS). It is often complicated to tell whether a spot is a consequence of a failure or points out the location of the defect itself. In this scenario, circuit simulators are a solution to resolve this ambiguity and ease this task. This work proposes a simulation method for circuits inspected using thermal laser stimulation techniques. Furthermore, simulations for the dynamic laser stimulation technique are proposed with encouraging results for failure analysis. Highlights: A simulation method to reproduce images acquired with Thermal Laser Stimulation techniques (such as OBIRCH, TIVA, DLS). Simulation for thermal laser stimulation speeds up the fault isolation step during a failure analysis, avoiding the image comparison between golden and faulty unit. Thermal laser stimulation simulation software enables validation of defect hypothesis, increasing the success rate of the analysis together with their accuracy.